2010
DOI: 10.1007/s11695-010-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Parameters, Weight Change and Improvement of Co-morbidities After Laparoscopic Roux Y Gastric Bypass and Laparoscopic Gastric Sleeve Resection—Comparative Study

Abstract: The laparoscopic Roux Y gastric bypass (LRYGB) and the laparoscopic gastric sleeve resection are frequently used methods for the treatment of morbid obesity. Quality of life, weight loss and improvement of the co-morbidities were examined. Match pair analysis of the prospectively collected database of the 47 gastric bypass and 47 gastric sleeve resection patients operated on in our hospital was performed. The quality of life parameters were measured with two standard questionnaires (SF 36 and Moorehead-Ardelt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 25 publications
2
12
0
4
Order By: Relevance
“…For example, Fezzi et al [21] demonstrated that LSG resulted in 57.18% EWL and used both WOQUOL-BREF and SF-36 measures to show that quality of life scores improved significantly after surgery, although such changes were not always associated with the amount of weight lost. Mohos et al [14] employed the SF-36 tool to evaluate changes in quality of life after submission to LRYBG and LSG and found that patients expressed high levels of satisfaction with both procedures, although those that had been treated by LRYBG perceived a better, but not statistically significant, quality of life compared with those submitted to LSG. while the main limitation is the short-term follow-up (12 months).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fezzi et al [21] demonstrated that LSG resulted in 57.18% EWL and used both WOQUOL-BREF and SF-36 measures to show that quality of life scores improved significantly after surgery, although such changes were not always associated with the amount of weight lost. Mohos et al [14] employed the SF-36 tool to evaluate changes in quality of life after submission to LRYBG and LSG and found that patients expressed high levels of satisfaction with both procedures, although those that had been treated by LRYBG perceived a better, but not statistically significant, quality of life compared with those submitted to LSG. while the main limitation is the short-term follow-up (12 months).…”
Section: Discussionmentioning
confidence: 99%
“…This can be measured using quality of life surveys such as short form health survey (SF-36) or Moorehead-Ardelt II (MA-II), which both take into account factors such as appearance, physical health, social functioning, mental health and so on. These surveys have both been used in studies looking at quality of life after bariatric procedures 18. Patients that feel that the improvement in their quality of life is not as much as expected may feel that the primary bariatric procedure was ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…The attainment and maintenance of good quality of life should be considered as one of the goals of bariatric surgery, and patients who fail to do so or perform persistently low on quality of life surveys post-operatively can be singled out as candidates that may benefit from revisional surgery. A study conducted by Mohos et al18 compared the quality of life of patients after primary and revisional laparoscopic Roux-en-Y gastric bypass (LRYGB) using both SF-36 and MA-II as measurements of quality of life. Although there was no statistically significant difference found between quality of life in both groups using either survey, the scores achieved by both groups corresponded to acceptable standards of quality of life as compared to the normal European population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, stomach leakage may cause severe consequences, such as infection and death, although the incidence rate of this complication is 2.4%. [ 3 ]…”
mentioning
confidence: 99%